Portfolio of CSA practices for scaling - Le Thi Tam; Simelton, Elisabeth (2018)
This publication showcases some of the indigenous and research-derived CSA technologies and practices (CSA T&P) developed and tested in My Loi Climate-Smart Village in Vietnam. Prepared by the World Agroforestry Centre Vietnam, four CSA T&Ps were identified for scaling, such as: orange-based agroforestry system, black pepper home garden, acacia-based agroforestry system, and vermiculture. For each CSA T&P, discussion includes the description of the practice, CSA indicators, farmer’s benefits, risks, scaling considerations (i.e., biophysical, socio-economic, and political factors), and cost and benefit analysis.